Disclosure das contingências e provisões passivas - Michelle Adriane Silva de Oliveira (2011)
The accounting landscape changes, both national and international, have been driving the search for greater disclosure by enterprises and investors. Due to the characteristics of companies listed on the "Novo Mercado da BM&FBovespa" a high disclosure level is expected from them as the compliance to regulatory agencies standards in regard thecontingential obligations and broadcast of the defining the company liability level, due diligence dates and uncertain circumstances. This present work has the goal of identify the disclosure level on the provisions and contingent passives as reported by the companies in the"Novo Mercado da MB&FBovespa" listing. To achieve this goal there have been analysis of the accounting numbers, administration reports and the external independent auditors on 2010 of those companies. The basis for the descriptive analysis of the characteristics of the contingential information on this work are result of the most used theories to support the discrimination of companies: "Agency Theory", "Report Theory", "Stakeholders Theory" and "Legitimacy Theory". The analyzed characteristics, coming from the documental analysis techniques, encompass the evidential classification (declarative, quantitative monetary, quantitative non-monetary, quantitative monetary and non-monetary) and information location (Consultant Reports, Administration Report, Accountant Demonstratives or Descriptive Bills). In order to explain the evidences of contingent as reported by theresearched companies individual factors have been taking in account such as size of actives, contingent relevance, amount of declarations on the subject. The results show that the disclosure level is medium for the provisions and low for the contigent passives. It was also verified that the tendency to report contingent facts isn't related to the active size nor thecontingent relevancy. The conclusion follows that the research results indicate the companies have voluntarily reported few information on their contingents.